Disulfiram Loaded Transdermal Nanoinvasomal Gel Using Carvacrol as Penetration Enhancer - Worood Hameed AL-Zheery ,; Hanan Jalal Kassab, (Iraqi Journal of Pharmaceutical Sciences, 2025)
Disulfiram (DSF), an FDA-approved pharmaceutical for the management of alcoholism, has demonstrated its efficacy against several kinds of cancer. DSF has limited solubility, fast metabolism, short duration of action, and instability in physiological environments, mostly caused by rapid degradation in the acidic gastric environment, Therefore, a transdermal gel containing disulfiram, which was loaded into invasomes, was developed to improve the stability of DSF and enable its effective distribution to tumor tissues. The optimal invasomal dispersion was developed in the laboratory using a 4:1 ratio of soya-phosphatidylcholine (SPC) to disulfiram, and 1% carvacrol as a penetration enhancer. Furthermore, three invasomal gel formulas (IV-g1, IV-g2, and IV-g3) have been developed using hyaluronic acid (HA) as the gelling agent at concentrations of 2%, 2.5%, and 3%. These formulations are subjected to further in-vitro evaluation to assess their physical appearance, homogeneity, viscosity, spreadability, and in-vitro drug release. Results indicated that the formula (IV-g3) exhibited better homogeneity, consistency, spreadability, and stability and showed a non-Newtonian flow and a drug content (99.6±0.4%). Compared to the DSF-suspension (16%), the IV-g3 showed a much greater release of DSF (90.03%). The ex-vivo skin permeation of rat abdomen skin for IV-g3 was significantly higher (14.72cm2/h ×10-3) than DSF-suspension's (3.44 cm2/h ×10-3) during an entire day. The enhancement ratio (ER) of IV-g3, which measured 4.27, surpassed that of the DSF suspension. The stability study indicated that there were no significant alterations in the characteristics of the formulation. The study successfully formulated a new transdermal gel by utilizing invasomal nanocarriers. This gel successfully promoted the delivery of DSF through the skin. The transdermal delivery approach exhibited improved stability of DSF, better skin permeability, and enhanced the efficacy of disulfiram.